ABU RAYHAN BERUNI'S VIEWS ON SOCIAL EXISTENCE AND KNOWLEDGE - Khandamova Marifat Akramovna (European Journal of Interdisciplinary Research and Development, 2022)
It is known that Abu Rayhan Beruni's views on social existence, according to researchers, have not yet been deeply researched. The important aspect of the scientist's views on social existence is that he, as an encyclopedist, sought to develop a method of studying the life of society. The article describes the analysis of Abu Rayhan Beruni's views on social existence and knowledge.